Obsessive-compulsive (anankastic) personality disorder: toward the ICD-11 classification - Fineberg, Naomi A.; Reghunandanan, Samar; Kolli, Sangeetha; Atmaca, Murad (Assoc Brasileira Psiquiatria, 2014)
Obsessive-compulsive personality disorder (OCPD) is an early-onset disorder characterized by perfectionism, need for control, and cognitive rigidity. Its nosological status is currently under review. Historically, OCPD has been conceptualized as bearing a close relationship with obsessive-compulsive disorder (OCD). In this article, we discuss the diagnosis of OCPD in anticipation of its review for the ICD-11, from the perspective of clinical utility, global applicability, and research planning. Considering the recent establishment of an obsessive-compulsive and related disorders (OCRD) category in DSM-5, we focus on the relationship between OCPD and the disorders that are currently thought to bear a close relationship with OCD, including DSM-5 OCRD, and other compulsive disorders such as eating disorder and autistic spectrum disorder (that were not included in the DSM-5 OCRD category), as well as with the personality disorders, focusing on nosological determinants such as phenomenology, course of illness, heritability, environmental risk factors, comorbidity, neurocognitive endophenotypes, and treatment response. Based on this analysis, we attempt to draw conclusions as to its optimal placement in diagnostic systems and draw attention to key research questions that could be explored in field trials.
Keywords: Personality disorders; avoidant-dependent-obsessive-compulsive-passive aggressive; obsessive-compulsive disorder; diagnosis and classification; models/theories of psychiatry